Monitoring and Analysis of Ground Settlement Induced by Tunnelling with Slurry Pressure-Balanced Tunnel Boring Machine - Hyunku Park; Ju-Young Oh; Dohyung Kim; Seokbue Chang (Advances in Civil Engineering)
A case study of monitoring and analysis of ground settlement caused by tunnelling of stacked twin tunnels for underground metro line construction through the densely populated area using the slurry pressure-balanced TBM is presented. Detailed ground settlement monitoring was carried out for the initial stage of down-track tunnelling in order to estimate trough width factor and volume losses including face, shield, and tail losses. In addition, using the gap model, prediction of volume loss and ground settlement was carried out with consideration of the ground condition, TBM configurations, and actual operation data. The predictions of the gap model were compared with the observed results, and adjustment factors were determined for volume loss estimation. The adjusted factors were applied to predict ground settlement of the up-track tunnel, and its results were compared with the field measurements.